(untitled) - Stahl, Bernd Carsten (Hersley, PA, 2004)
Responsible Management of Information Systems discusses the question how can information systems be used and managed in a responsible manner. It does so by first defining the central concepts of information systems as the business use of information technology and the underlying concepts of ethics and morality. The term responsibility is introduced as a mediation of ethics and morality and a promising approach to normative questions. After demonstrating that the traditional notion of responsibility runs into many problems when applied to information systems the book develops a new, a reflective theory of responsibility. This theory that emphasizes the central characteristics of responsibility, namely openness, consequentialism, and teleology, is then applied to normative problems in information systems. It is shown that with the use of this theory the central moral and legal problems of information systems such as privacy or intellectual property can be successfully addressed.
Keywords: Information resources management,Information technology,Business ethics,Social responsibility of business; Moral and ethical aspects,Moral and ethical aspects